2015
DOI: 10.1152/physrev.00032.2014
|View full text |Cite
|
Sign up to set email alerts
|

The Physiology of ProteinS-acylation

Abstract: Protein S-acylation, the only fully reversible posttranslational lipid modification of proteins, is emerging as a ubiquitous mechanism to control the properties and function of a diverse array of proteins and consequently physiological processes. S-acylation results from the enzymatic addition of long-chain lipids, most typically palmitate, onto intracellular cysteine residues of soluble and transmembrane proteins via a labile thioester linkage. Addition of lipid results in increases in protein hydrophobicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
359
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(364 citation statements)
references
References 296 publications
5
359
0
Order By: Relevance
“…Although there is no simple consensus sequence for palmitoylation, algorithms predict that more than 50% of human ion channels are palmitoylated (for reviews, see Refs. 22,26,and 27). Published studies have provided evidence for palmitoylation of numerous voltage-gated channels (e.g.…”
Section: Edited By Henrik G Dohlmanmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no simple consensus sequence for palmitoylation, algorithms predict that more than 50% of human ion channels are palmitoylated (for reviews, see Refs. 22,26,and 27). Published studies have provided evidence for palmitoylation of numerous voltage-gated channels (e.g.…”
Section: Edited By Henrik G Dohlmanmentioning
confidence: 99%
“…Cys palmitoylation of soluble and transmembrane proteins is a reversible post-translational modification that increases protein surface hydrophobicity, facilitating interactions with membranes and/or other proteins (22)(23)(24)(25)(26). Although there is no simple consensus sequence for palmitoylation, algorithms predict that more than 50% of human ion channels are palmitoylated (for reviews, see Refs.…”
Section: Enacsmentioning
confidence: 99%
“…Having previously reported that CSE of R1 and R2 is around 60% and 20% in quiescent cells 200 we next sought to investigate a role for palmitoylation in modulation of CSE of R1 and R2, given the recognized role of palmitoylation in regulation of receptor trafficking 209 . We used flow cytometry to determine CSE of the receptors expressed transiently in CHO and HEK293 cells as above.…”
Section: Palmitoylation Of R1 and R2 Is Required For Cell Surface Expmentioning
confidence: 99%
“…In the current study we set out to investigate the putative role of a 'housekeeping' PTM, Spalmitoylation, which has been shown to influence the cellular homeostasis and regulation of a variety of proteins and receptors at multiple levels 209,210 . S-palmitoylation is a reversible lipid modification involving the addition of a saturated 16-carbon palmitate moiety to specific cysteines via a thioester linkage that may, like phosphorylation or ubiquitination, act as a switch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation